Novel pyrrolo-1,5-benzoxazepine compounds display significant activity against resistant chronic myeloid leukaemia cells in vitro, in ex vivo patient samples and in vivo - ZISTERER, DANIELA MARIA; WILLIAMS, DAVID CLIVE; MC ELLIGOTT, TONY (Nature, 2010)
Background: Imatinib is a direct and potent inhibitor of the constitutively active tyrosine kinase, breakpoint cluster region-Abelson (Bcr-Abl), which is central to the pathogenesis of chronic myeloid leukaemia (CML) patients. As such, imatinib has become the front-line treatment for CML patients. However, the recent emergence of imatinib resistance, commonly associated with point mutations within the kinase domain, has led to the search for alternative drug treatments and combination therapies for CML. Methods: In this report, we analyse the effects of representative members of the novel pro-apoptotic microtubule depolymerising pyrrolo-1,5-benzoxazepines or PBOX compounds on chemotherapy-refractory CML cells using a series of Bcr-Abl mutant cell lines, clinical ex vivo patient samples and an in vivo mouse model. Results: The PBOX compounds potently reduce cell viability in cells expressing the E225K and H396P mutants as well as the highly resistant T315I mutant. The PBOX compounds also induce apoptosis in primary CML samples including those resistant to imatinib. We also show for the first time, the in vivo efficacy of the pro-apoptotic PBOX compound, PBOX-6, in a CML mouse model of the T315I Bcr-Abl mutant. Conclusion: Results from this study highlight the potential of these novel series of PBOX compounds as an effective therapy against CML.
PUBLISHED
Keywords: Oncology; Leukaemia; PBOX compounds